An unstable variant of GAP43 leads to neurodevelopmental deficiency - Mariko Noda; Ayumi Matsumoto; Hidenori Ito; Masayo Kagami; Toshihiro Tajima; Takayoshi Matsumura; Takanori Yamagata; Koh-ichi Nagata (Scientific Reports)
Abstract Growth-associated protein 43 (GAP43) is a membrane-associated phosphoprotein predominantly expressed in the nervous systems, and controls axonal growth, branching, and pathfinding. While the association between GAP43 and human neurological disorders have been reported, the underlying mechanisms remain largely unknown. We performed whole exome sequencing on a patient with intellectual disability (ID), neurodevelopmental disorders, short stature, and skeletal abnormalities such as left–right difference in legs and digital deformities, and identified a heterozygous missense variation in the GAP43 gene [NM_001130064.2: c.436G > A/p.(E146K)]. The variant GAP43 protein was unstable in primary cultured cortical neurons and hippocampal neurons in vitro. In utero electroporation of the variant protein also confirmed its instability in vivo, suggesting that the variant led to a condition similar with haploinsufficiency in the patient. Silencing of GAP43 via in utero electroporation of RNAi vectors demonstrated that loss of GAP43 suppressed axon elongation into the contralateral hemisphere and impaired the dendritic arbor formation as shown by decreased dendritic branch points and shortened total dendritic lengths. Collectively, these findings confirmed the critical roles of GAP43 in brain development and the pathological basis of GAP43-associated diseases. Our study will contribute to a better understanding of how dysregulation of GAP43 leads to human diseases.